The Urgency of Legal Justice for Society Against the Expansion of the Authority of Judges From a Criminal Law Perspective - Cahyani, Indah Fitri; Nnawulezi, Uche; Chinyere Constance, Ogah (IJCLS (Indonesian Journal of Criminal Law Studies), 2023)
Expansion of the authority of judges in the RKUHP is an interesting discussion where this is related to guaranteeing legal certainty for the community. The purpose of this research is to examine more deeply the impact of expanding the authority of judges in the RKUHP on legal certainty. The method used is a qualitative method. Then for this type of research using literature study by collecting journal articles related to the title being studied. The results of this study indicate that the expansion of authority in the form of judicial pardon is a means for realizing a balance between legal certainty and justice for the community, both of which are closely related to one another. In the RKUHP, the existence of the judge's pardon principle indicates a more flexible nature in criminal law. Unlike in the western Criminal Code which is more rigid. It is feared that this flexible nature will lead to more acts of fraud by law enforcers. In real terms, crime in Indonesia is increasingly modern. So that right now it really needs a legal system that is firm and able to provide legal certainty for its citizens. Studies related to the expansion of the judge's authority which are classified as increasingly flexible in the RKUHP are very important to do. Judicial Pardon is expected to be able to provide a balance between legal certainty and legal justice.